Brazilian Society for the History of Education: constitution, organization and achievements - Saviani, Dermeval (2012)
The text presents the trajectory of the Brazilian Society for the History of Education (Sociedade Brasileira de História da Educação-SBHE) since its foundation in 1999 until 2011. It starts by discussing the constitution of the field of History of Education in Brazil and the presentation of the first research groups, originated in the 1980s, which fostered the seminal discussions that stimulated the constitution of the SB HE. Next, it presents both the process of establishing the Brazilian Society for the History of Education and the main principles expressed in its statutes. The main achievements of the SB HE are also presented, such as the Brazilian Congress of History of Education, the Brazilian Review of History of Education and other publications edited by the Society. Lastly, the text presents an analysis of the perspectives that have been opened in the field related to historical- educational investigations in Brazil and the importance of the international exchanges that have been implemented in the last years stimulated by the SBHE.